Interworld - Gaiman, Neil; Reaves, Michael (HarperTeen, 2013)
At nearly fifteen years of age, Joey Harker learns that he is a Walker, able to travel between dimensions, and soon joins a team of different versions of himself, each from another dimension, to fight the evil forces striving to conquer all the worlds.